Dampak Adanya Industri Mente (CV. Mente Bali Sejahtera) terhadap Kondisi Sosial Ekonomi Petani Jambu Mente di Desa Ban, Kecamatan Kubu, Kabupaten Karangasem - MAHADEWI, NI LUH PUTU SRI; DIARTA, I KETUT SURYA; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p37, 2022)
Impact of Cashew Industry (CV. Mente Bali Sejahtera) on Socio Economic Conditions of Cashew Farmers in Ban Village, Kubu District, Karangasem Regency.  The existence of cashew industry (CV. Mente Bali Sejahtera) in Ban Village has slowly raised the social economic status of the community, especially farmers and alleviated poverty in Ban Village. Ban village is a dry area with clean water being very difficult to obtain. Such natural conditions make the people here work as cashew farmers. The purpose of the study was to analyze the impact of the cashew industry (CV. Mente Bali Sejahtera) on the socio-economic conditions of cashew farmers in Ban Village. The analytical method used is descriptive qualitative and quantitative using a before after approach, research instruments in the form of interview guidelines and questionnaires. The results showed that the impact of the cashew industry (CV. Mente Bali Sejahtera) on the economic conditions of farmers in Ban Village was an increase in income from before. Increased income has an impact on the ability of farmers to improve housing conditions so that they become more feasible and comfortable, and are able to create business opportunities so that they can provide other financial benefits. The impact of industry on social conditions shows that social interaction remains well established but there is a decrease in the intensity of meeting within the family because more interactions are carried out at night after work. The fulfillment of consumption and ownership of living facilities in the household has increased and the knowledge and skills of farmers are increasing. Suggestions that can be given are for farmers to pay more attention to their agriculture so that they can produce superior quality cashew nuts and the industry to pay attention to the comfort of the community to avoid conflicts.